2008
DOI: 10.2527/jas.2007-0499
|View full text |Cite
|
Sign up to set email alerts
|

Effect of sodium butyrate on growth performance and response to lipopolysaccharide in weanling pigs1

Abstract: Two experiments were conducted to determine the effects of dietary sodium butyrate on growth performance and response to Escherichia coli lipopolysaccharide (LPS) in weanling pigs. In a 28-d experiment, 180 pigs (initial BW 6.3 kg) were fed 0, 0.05, 0.1, 0.2, or 0.4% sodium butyrate, or 110 mg/kg of dietary tylosin. There was no effect of dietary sodium butyrate or tylosin on overall G:F, but there was a linear trend (P < 0.07) toward decreased ADFI and ADG as levels of sodium butyrate increased. In a second 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
28
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(39 citation statements)
references
References 31 publications
6
28
2
Order By: Relevance
“…The positive effect on bones may results from decreasing the levels of TNF-α and IL-6. This is in line with the study of Weber and Kerr (35), who concluded that sodium butyrate may regulate the response to inflammatory stimuli in weaning pigs challenged with Escherichia coli lipopolysaccharide.…”
Section: Discussionsupporting
confidence: 77%
“…The positive effect on bones may results from decreasing the levels of TNF-α and IL-6. This is in line with the study of Weber and Kerr (35), who concluded that sodium butyrate may regulate the response to inflammatory stimuli in weaning pigs challenged with Escherichia coli lipopolysaccharide.…”
Section: Discussionsupporting
confidence: 77%
“…Worse results were received by Biagi et al (2007). In their experiment sodium butyrate did not improve piglet performance and in the experiment of Weber and Kerr (2008) butyrate lowered piglet body weight gains and feed utilization.…”
Section: Introductionmentioning
confidence: 88%
“…Salts of acids are also less corrosive and may be more soluble in water than free acids (Partanen & Mroz, 1999). Although beneficial effects have been reported from trials using supplements of salts in pig diets (Table 3), other studies have not introduced any positive effects (Biagi et al 2007;Weber & Kerr, 2008 (Hardy 2002;Franco et al 2005;Partanen et al 2007;Kasprowicz-Potocka et al 2009). Table 2.…”
Section: Introductionmentioning
confidence: 93%